Assessing the Pharmacological Potential of Thymoquinone for Managing Alcohol Craving and Withdrawal Syndrome in Mice - Sarmad, Mohammad Arsalan; Ramana, Muttavarapu Venkata; Khurana, Navneet (Indian Journal of Pharmaceutical Education and Research, 2025)
Aim/Background The aim is to evaluate THMQ’s impact on alcohol withdrawal and alcohol craving using an animal model. Mice were exposed to increasing ethanol doses to simulate dependency. Researchers assessed anxiety levels during withdrawal using behavioural and biochemical tests. THMQ was administered orally at 20 mg/kg and 40 mg/kg, compared to diazepam (1 mg/kg). Materials and Methods Model Creation Mice received escalating ethanol doses (5% to 35% v/v) over specific days. Regular water was given during withdrawal periods. Assessment Tools Elevated Plus Maze (EPM), Elevated Zero Maze (EZM), Open Field Test (OFT), and Western Blot analysis. Treatment Intervention: THMQ (20 mg/kg and 40 mg/kg) vs. diazepam (1 mg/kg). Results and Conclusion THMQ-treated group showed reduced anxiety and alcohol desire. Alcohol consumption decreased in THMQ-treated mice. No changes in GluA1 and sk2 protein levels. THMQ holds promise as a remedy for alcohol cravings and withdrawal symptoms
Keywords: Alcohol Craving; Alcohol Withdrawal; Thymoquinone; Western blot; Open Field Test